First description of female of Haplosialodes liui Huang et al., 2016 (Megaloptera: Sialidae) from Cretaceous Burmese amber - Liu, Xingyue; Lu, Xiumei; Xia, Fangyuan; Wang, Bo (Zootaxa, 2017)
A female of the alderfly species, Haplosialodes liui Huang et al., 2016, from the mid-Cretaceous Burmese amber is described for the first time. Systematic position of the genus Haplosialodes Huang et al., 2016 is briefly discussed.